SUNNAH SEBAGAI SUMBER HUKUM DALAM BACAAN KONTEMPORER MUHAMMAD SYAHRUR - ARIP PURKON (Al Qalam, 2012)
Sunna, based on the Islamic Law perspective, has a fundamental role and position. Sunna is one if Islamic Law sources. It always becomes an object of scientific study because it covers God and human aspects. Many studies on Sunna have been studied by many scholars. Muhammad Syahrur, a Syrian intellectual, is one ef scholars who tries to restudy the concept of Sunna. He views that all this time, there is a Jew mistakes of understanding on Sunna among Muslims. He divides Sunna into two categories, sunna risalah and sunna nubuwwah. The former is eternal while the later is sunna dealing with knowledge so that it may change quite the thing. Such a division is an effort to differentiate between transcendent aspect and profane asped in Sunna. Key Words : Sunna, Treatise, Nubuwwah.